ANALISIS STRATEGI KEBIJAKAN MUTU DAN STANDAR PRODUK KAYU LAPIS DALAM RANGKA MENINGKATKAN DAYA SAING EKSPOR - Widyastutik, Widyastutik; Arianti, Reni Kristina (Jurnal Agribisnis Indonesia, 2014)
Developed countries use a standard as instrument to conduct trade barriers. The issues about quality and standard are also applicated to Indonesian plywood exports. Consumer countries led to the requirements of the international timber legality, for example USA with Amandemen Lacey Act, Uni Eropa with EU Timber Regulation, Australia with Prohibition Bill, and Japan with Green Konyuho. Standard is a main instrument to increase of competitiveness. The aims of this study are: (1) to analyze the competitiveness of Indonesia plywood in the major export destinations, (2) to analyze strategy of policies to improve the quality and standard of plywood in order to increase competitiveness. The analytical methods used in this study are Revealed Comparative Advantage and Analytical Hierarchy Process. The result of study shows that an average value RCA between Indonesia and UK is high. According to AHP, government should facilitate exporter to solve the problem in the cost of certificate of plywood legalcy (SVLK).